Organophotoredox Catalysis: Visible-light-induced Multicomponent Synthesis of Chromeno[4, 3-b]chromene and Hexahydro-1H-xanthene Derivatives - Sharma, Amit K.; Tiwari, Jyoti; Jaiswal, Deepali; Singh, Shailesh; Singh, Jaya; Singh, Jagdamba (Current Organocatalysis, 2019)
Background: In recent years, photoredox catalysis using eosin Y has gained considerable significance in organic chemistry. It is evolving as a powerful approach in modern organic synthesis for the activation of small molecules. Objective: The use of organic dyes to convert visible light into chemical energy by involving a single-electron transfer with organic substrates has innumerable applications. Method and Results: The present strategy is the first example of visible light promoted, aerobic, oxidative cyclization of chromeno[4,3-b]chromenes and hexahydro-1H-xanthenes via the formation of C–O and C–C bonds to afford excellent yield of the products in a simple one-pot operation under mild reaction conditions. Conclusion: The major advantages of the present methodology include short reaction time, cost effectiveness, easy work-up, broad substrate scope and high atom economy.
Keywords: synthesis